Asimetri Transmisi Kebijakan Moneter Ganda Terhadap Nilai Tukar Rupiah: Pendekatan Nardl - Heru Setyowiyono; Lina Trisnawati; Aina Izzati Zuhria; Sarirotul 'Alim; Rokhmat Subagiyo (Politeknik Ganesha Medan, 2026)
Fluctuations in the Indonesian rupiah exchange rate within the context of a dual financial system highlight the critical role of monetary policy in maintaining macroeconomic stability. This study aims to analyze the effects of conventional and Islamic monetary policy instruments on the rupiah exchange rate while accounting for external factors. The analysis employs the Nonlinear Autoregressive Distributed Lag (NARDL) model using monthly time series data from 2016 to 2025, covering the rupiah exchange rate, BI Rate, PUAS, inflation, and the Federal Reserve interest rate. The results indicate that these variables significantly influence the rupiah exchange rate in both the short and long run, with evidence of long-run cointegration among the variables. However, the asymmetric test results reveal no significant differences in the response to increases and decreases in the BI Rate and PUAS. These findings suggest that although the dual monetary system plays a role in exchange rate stability, market responses tend to be symmetric with respect to monetary policy changes.